2020
DOI: 10.1111/geb.13086
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of predicted plant trait distributions at the global scale

Abstract: AimPredictions of plant traits over space and time are increasingly used to improve our understanding of plant community responses to global environmental change. A necessary step forward is to assess the reliability of global trait predictions. In this study, we predict community mean plant traits at the global scale and present a systematic evaluation of their reliability in terms of the accuracy of the models, ecological realism and various sources of uncertainty.LocationGlobal.Time periodPresent.Major taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 59 publications
6
90
0
Order By: Relevance
“…High plant height and large seed size are adaptative in hot, moist, resource rich environments where biotic competition is high (Moles 2018; Boonman et al . 2020), height is important in competing for light, and larger seeds show higher establishment under biotic competition and shade (Westoby et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…High plant height and large seed size are adaptative in hot, moist, resource rich environments where biotic competition is high (Moles 2018; Boonman et al . 2020), height is important in competing for light, and larger seeds show higher establishment under biotic competition and shade (Westoby et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We found that nonlinear responses of St to cross‐site biotic and abiotic factors were prevalent, suggesting the linear framework conventionally used in stemflow studies may not be adequate. The development of more advanced nonparametric and machine learning approaches in recent years has opened new ways of describing patterns as well as investigating nonlinear processes in ecological studies (Boonman et al, 2020; Wuest et al., 2020). This is well exemplified in our synthesis using BRT, which quantified the relative contribution of each individual predictor to global St and provided a mechanistic understanding of how they affect St (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The available dataset of species presence/absence permits the use of indices computed with binary data, namely FRic and FRed. Articles on functional diversity consisting of binary data sets have been published on riparian vegetation (Sonnier et al, 2014;Brice et al, 2017) and those datasets have been considered as reliable for predicting plant trait distributions globally (Boonman et al, 2020). In a conceptual study with an illustrated ecological hypothesis, Boersma et al (2016) stated that presence/absence data can serve to make the most straightforward interpretation of the results when disturbance acts as an environmental filter.…”
Section: Limitationsmentioning
confidence: 99%